Child Rights Violation in Iweala’s Beasts of No Nation: A Study of Traumatic Experience of Child Soldier Agu - Pant, Rajendra Prasad; Gajurel, Amisha (KMC Journal, 2024)
This paper examines various aspects of the life of protagonist Agu and other child soldiers evolved in the war in Uzodinma Iweala’s novel, Beasts of No Nation. The concern of this paper is to explore the after-effects of West African Freedom War on the life of children from the perspective of child soldiers. The effects of trauma on the ruined life of child soldiers in their post war life formulate their social status regarding future generation too. The question of child right during guerilla war in unnamed West African country is the major concern of the novel including other factors those have serious impact upon the lives of the people living in West Africa. The research tool used for research is traumatic effects for the development of psychology in life of people with reference to Cathy Caruth, Van der Kolk and Ruth Leys. The research methodology used for analysis is library research textual analysis. The major finding is that the study of the discourse of traumatic effects of child rights violations that Iweala builds up in Beasts of No Nation with the psychological nuances creating mental disorder in the life of child soldiers. It tries to do so through a spotlight on how the novel presents trauma as post-war life experience of children where the traumatic experience distorts life of children.</